2002
DOI: 10.1007/s00122-002-1036-8
|View full text |Cite
|
Sign up to set email alerts
|

Expression and inheritance of the wheat Glu-1DX5 gene in transgenic maize

Abstract: We have produced transgenic maize plants containing a wheat Glu-1Dx5 gene encoding the high-molecularweight glutenin subunit 1Dx5. Analysis by SDS-PAGE showed that a protein similar in size to the wheat 1Dx5 subunit accumulates in the endosperm of transgenic maize from four independent transformation events. This protein reacts with a monoclonal antibody specific to the wheat 1Dx5 subunit and was not detected in nontransgenic controls or in pollen, anthers, leaves or embryos of plants grown from seeds expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 30 publications
(35 reference statements)
0
18
0
1
Order By: Relevance
“…Although the Pin promoters have not been evaluated in any species other than wheat and rice, we have previously reported evidence that another seed-specific promoter of wheat, the Glu-1D-1 promoter encoding the high molecular weight subunit of glutenin 1D·5, is expressed in pollen when used to drive transgene expression in barley (Zhang et al 2001). The 1D·5 transgene is also inefficiently transmitted through the pollen in transgenic maize and one explanation could be that the gene is expressed in the pollen resulting in mortality (Sangtong et al 2002). Hence we do not consider that it is possible to draw valid conclusions about gene expression patterns based on transgene expression in other species, even between related cereals such as barley, wheat, maize and rice.…”
Section: Discussionmentioning
confidence: 92%
“…Although the Pin promoters have not been evaluated in any species other than wheat and rice, we have previously reported evidence that another seed-specific promoter of wheat, the Glu-1D-1 promoter encoding the high molecular weight subunit of glutenin 1D·5, is expressed in pollen when used to drive transgene expression in barley (Zhang et al 2001). The 1D·5 transgene is also inefficiently transmitted through the pollen in transgenic maize and one explanation could be that the gene is expressed in the pollen resulting in mortality (Sangtong et al 2002). Hence we do not consider that it is possible to draw valid conclusions about gene expression patterns based on transgene expression in other species, even between related cereals such as barley, wheat, maize and rice.…”
Section: Discussionmentioning
confidence: 92%
“…Endosperm powder samples were collected from transgenic kernels using a hand-held drill as described by Sangtong et al (2002). Plant materials were incubated with the following protein extraction buffer at a rate of 10 μl buffer mg −1 maize powder: 25 mM sodium phosphate (pH 6.6), 100 mM NaCl, 0.1% Triton X-100 (v/v), 1 mM EDTA, 10 μg ml −1 leupeptin, and 0.1 mM serine protease inhibitor Perfabloc SC (Fluka), for 2 h at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
“…For example, C-terminal fusion of a signal KDEL (Lys-Asp-Gl u-Leu) resulted to a 100-fold increase in expression levels of an scFv antibodies in plants (Schouten et al, 1996;Torres et al, 2001). Also, high expression levels of Ô-zeins were detected in tobacco for ô-zein constructs that contain KDEL compared to those constructs that did not contain KDEL (Belluci et al, 2000) Other amino acid motifs such as HDEL (Pueyo et al, 1995) and SEKDEL (Chikwamba et al, 2002) have been reported to increase the levels of recombinant proteins in plants. Extended retention in the ER is thought to promote correct protein folding leading to higher stability and accumulation of proteins (Schouten et al, 1998).…”
Section: Jj Torgefmg Wwfmentioning
confidence: 99%
“…In general, the male gamete is more prone to deleterious effects than the female gamete (Zhong, 1998). The reduced gamete transmission may result in the absence of, or fewer homozygous transgenic progeny than expected (Sangtong et al, 2002).…”
Section: Dwwgemg Frafwvmzandho/zmentioning
confidence: 99%